Enhancing Students' Critical Thinking in Mathematics Education: A Systematic Literature Review - Nafiah, Siti; Kusumah, Yaya S; Dahlan, Jarnawi Afgani (FKIP Universitas Lampung, 2024)
Students' critical thinking abilities are one of the goals of 21st-century learning. Critical thinking abilities enable students to think in a realistic and logical way, assist in understanding and solving problems, and build effective communication skills in facing future challenges. Therefore, the aim of this Systematic Literature Review (SLR) is to identify effective methods for enhancing students' critical thinking abilities, especially in the study of mathematics education. Microsoft Excel and Publish or Perish were used to examine a total of 14 papers from 2014 to 2024 found using Google Scholar and Scopus. The results of the analysis show that teaching approaches, subject matter, and teacher attitudes are some of the methods used to improve critical thinking skills. The most popular and successful teaching method in mathematics education is problem-based learning (PBL). Additionally, research conducted between 2020 and 2022 shows a greater focus on critical thinking skills, with quantitative and qualitative research methodologies taking center stage. Teachers can use these insights to provide more imaginative and significant mathematics instruction. It is recommended that teachers develop modules and frameworks that are integrated with ICT to improve critical thinking skills, especially for teaching in the early grades. This can contribute to a more imaginative and meaningful mathematics learning process. Keywords: critical thinking, SLR, learning methods. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1925-1938